Compiler construction - Louden, Kenneth C. (New Delhi Cengage Learning, 1997)
Compiler Construction: Principles and Practice features a comprehensive, hands-on case study project for constructing an actual, working compiler. This case study involves a relatively simple programming language that will expose readers to the basic concepts used (and potential pitfalls) in constructing larger compilers. Kenneth Louden and his colleagues at San Jose State University have successfully class-tested this approach. Professionals joining or beginning a compiler project will find Compiler Construction valuable, as it provides the basic theory, necessary tools, and practical experience to design and program an authentic compiler.
Keywords: Compilers (Computer programs); Compiling (Electronic computers); Computer science